2002
DOI: 10.1183/09031936.02.00012902
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial tracheobronchitis in mechanically ventilated patients: incidence, aetiology and outcome

Abstract: The aim of this study was to determine the incidence, the organisms responsible for and the impact on outcome of nosocomial tracheobronchitis (NTB) in the intensive care unit (ICU).This prospective observational cohort study was conducted in a 30-bed medical/ surgical ICU over a period of 6.5 yrs. All patients ventilated for w48 h were eligible. Patients with nosocomial pneumonia (NP) without prior NTB were excluded. Patients with first episodes of NTB were compared with those without NTB by univariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
196
2
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 30 publications
6
196
2
13
Order By: Relevance
“…PCT is commonly used as an inflammatory marker and is useful for predicting the prognosis and deciding whether to use antibiotics in pneumonia [28,29]. Nosocomial tracheobronchitis is common in mechanically ventilated ICU patients [30]. A recent paper reported that approximately one third of ventilator-associated tracheobronchitis (VAT) patients later developed ventilator-associated pneumonia (VAP) [31].…”
Section: Discussionmentioning
confidence: 99%
“…PCT is commonly used as an inflammatory marker and is useful for predicting the prognosis and deciding whether to use antibiotics in pneumonia [28,29]. Nosocomial tracheobronchitis is common in mechanically ventilated ICU patients [30]. A recent paper reported that approximately one third of ventilator-associated tracheobronchitis (VAT) patients later developed ventilator-associated pneumonia (VAP) [31].…”
Section: Discussionmentioning
confidence: 99%
“…In mechanically ventilated patients, nosocomial tracheobronchitis has been associated with a longer ICU stay and time on the ventilator, without increased mortality (158). In one randomized trial of intubated patients with communityacquired tracheobronchitis, antibiotic therapy resulted in a decreased incidence of subsequent pneumonia and mortality (156).…”
Section: Diagnosis Clinical Diagnosismentioning
confidence: 99%
“…Purulent sputum may be caused by tracheobronchitis and does not always signify parenchymal involvement. 48 Infiltrates on the chest Risk factors for the development of ventilator associated pneumonia N Age >60 years N Severity of illness (APACHE II score .16) N Acute or chronic lung disease N Excessive sedation N Enteral nutrition N Severe burns N Supine body position N Glasgow coma scale,9 N Use of muscle relaxants N Cigarette smoking radiograph can be caused by a number of non-infective conditions including pulmonary oedema, haemorrhage, and contusions. 49 A study by Meduri and colleagues highlighted some of these difficulties.…”
Section: Diagnosis Of Vapmentioning
confidence: 99%